Therapeutic Implications of Renin-Angiotensin System Modulators in Alzheimer's Dementia - Daniela-Carmen Ababei; Veronica Bild; Ioana Macadan; Alexandru Vasincu; Răzvan-Nicolae Rusu; Mihaela Blaj; Gabriela Dumitrița Stanciu; Radu-Marian Lefter; Walther Bild (MDPI AG, 2023)
The Renin-Angiotensin System (RAS) has attracted considerable interest beyond its traditional cardiovascular role due to emerging data indicating its potential involvement in neurodegenerative diseases, including Alzheimer's dementia (AD). This review investigates the therapeutic implications of RAS modulators, specifically focusing on angiotensin-converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs), and renin inhibitors in AD. ACEIs, commonly used for hypertension, show promise in AD by reducing angiotensin (Ang) II levels. This reduction is significant as Ang II contributes to neuroinflammation, oxidative stress, and β-amyloid (Aβ) accumulation, all implicated in AD pathogenesis. ARBs, known for vasodilation, exhibit neuroprotection by blocking Ang II receptors, improving cerebral blood flow and cognitive decline in AD models. Renin inhibitors offer a novel approach by targeting the initial RAS step, displaying anti-inflammatory and antioxidant effects that mitigate AD degeneration. Preclinical studies demonstrate RAS regulation's favorable impact on neuroinflammation, neuronal damage, cognitive function, and Aβ metabolism. Clinical trials on RAS modulators in AD are limited, but with promising results, ARBs being more effective that ACEIs in reducing cognitive decline. The varied roles of ACEIs, ARBs, and renin inhibitors in RAS modulation present a promising avenue for AD therapeutic intervention, requiring further research to potentially transform AD treatment strategies.